PERAMALAN DAN PENENTUAN WAKTU PEMESANAN KEMBALI YANG OPTIMAL DENGAN METODE EXPONENTIAL SMOOTHING DAN METODE ECONOMIC ORDER QUANTITY (STUDI KASUS SUMBER MAKMUR) - Sukamdani, Ryan Rici; Herwindiati, Dyah Erny; Sutrisno, Tri (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
Application for forcasting the number of items the next day, determining optimal revervation time and determine the optimal number of or reorder items by using the method Single Exponential Smoothing, Double Exponential Smoothing, Economic Order Quantity(EOQ), and Reorder Quantity(ROP). This method was created for Store Sumber Makmur. Store Sumber Makmur is a shop that sells motorcycle tools, equipment, parts, accessories, lubricating oil, maintaince, and motorcycle repair services. There are  programming languages used to make this application, namely PHP.  php for the user interface and python for the calculation. Testing was done by User Acceptence Testing (UAT) and testing of data. UAT testing for check buttons and features